The Impact of Economic Growth and Electricity Access on CO₂ Emissions in Bangladesh: An ARDL Bounds Testing Approach - Pande, Saikat (Journal of Environmental Science and Economics, 2025)
As a rapidly developing nation, Bangladesh faces the imperative of decoupling economic expansion from environmental degradation. This study investigates the dynamic interplay between economic drivers, non-CO₂ greenhouse gases, and carbon dioxide (CO₂) emissions using annual data from 1990 to 2022. Employing the Autoregressive Distributed Lag (ARDL) bounds testing approach, the model examines the impact of GDP growth, electricity access, foreign direct investment (FDI), trade liberalization, and emissions from methane (CH₄) and nitrous oxide (N₂O). The empirical results substantiate a stable long-run cointegrating relationship among these variables. Specifically, long-term CO₂ emissions are significantly driven by GDP growth and methane output, whereas Foreign Direct Investment (FDI) is associated with a reduction in emissions. In the short run, however, expanded electricity access, industrial value added, and nitrous oxide levels contribute to rising pollution. The Error Correction Term (ECT) of -0.273 indicates a moderate adjustment speed, correcting approximately 27.3% of disequilibrium annually. These findings underscore the need for a multifaceted policy framework, including 'Green FDI' initiatives, accelerated renewable energy adoption, industrial energy efficiency, and sustainable agriculture. Implementing these measures will help Bangladesh align its development trajectory with SDGs 7, 8, and 13.